Globicephala melas - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Globicephala mêlas (Traill, 1809). Nicholson's J. Nat. Philos. Chem. Arts, 22:81. TYPE LOCALITY: UK, Scotland, "in Scapay Bay, in Pomona, one of the Orkneys". DISTRIBUTION: North Atlantic and southern Oceans: cold-temperate waters. Kasuya (1975) described the historic distribution in the NW Pacific. STATUS: CITES - Appendix II. SYNONYMS: edwardii, giobiceps, leucosagmaphora, svineval. COMMENTS: See Van Bree (1971). Formerly called G. melaena but Article 31b of the third edition of the International of Zoological Nomenclature (1985) specifically gave mêlas as an example of a Greek adjective that does not change its ending when transferred to a genus of another gender (see Schevill, 1990«, b; Rice, 1990). Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 352, DOI: 10.5281/zenodo.7352970